If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -7(3x + -1) = -4x + 28 Reorder the terms: 4 + -7(-1 + 3x) = -4x + 28 4 + (-1 * -7 + 3x * -7) = -4x + 28 4 + (7 + -21x) = -4x + 28 Combine like terms: 4 + 7 = 11 11 + -21x = -4x + 28 Reorder the terms: 11 + -21x = 28 + -4x Solving 11 + -21x = 28 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 11 + -21x + 4x = 28 + -4x + 4x Combine like terms: -21x + 4x = -17x 11 + -17x = 28 + -4x + 4x Combine like terms: -4x + 4x = 0 11 + -17x = 28 + 0 11 + -17x = 28 Add '-11' to each side of the equation. 11 + -11 + -17x = 28 + -11 Combine like terms: 11 + -11 = 0 0 + -17x = 28 + -11 -17x = 28 + -11 Combine like terms: 28 + -11 = 17 -17x = 17 Divide each side by '-17'. x = -1 Simplifying x = -1
| 127=(16*59.3/x)(16*9.9/x) | | p-8=-15/p | | -6x+7+7x=9 | | x-sqrt(11-10x)=-22 | | 10xwhat=990 | | 4x+6=4+3x | | 5t-9=31 | | 7k-5=30 | | 6a-5=43 | | -30-6a=2(1-7a) | | 7a^2-24a-4=0 | | 31+6n=-5(1-3n) | | 4(2)-3/2(1)-1 | | 2x+26=0 | | -9+2x+4x=9 | | 5x-6x-3=-5 | | 6+4(3-2n)=-4n+14 | | 1/6=1.5x | | 8y=-3x+4 | | 5b-2=18 | | 52x^3-122x^2+66x=0 | | -2n=6-2n | | -8x+8+5x=2 | | -3x+3=2 | | 6x+4.50y=45 | | 20.4/3.4= | | 2x/9-9/3=8-3x | | 6(x-2)+5x=9x-2(4-3) | | 9x+4=64 | | -7x+2y=70 | | .66x-6+3=4x-4 | | 4.5*4.4= |